MONITORING OF VERTICAL DISPLACEMENTS OF THE EARTH SURFACE OF THE RIGHT BANK OF THE KANIV RESERVOIR - ORLENKO, Tetiana (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Monitoring of vertical displacements of the earth's surface on the right bank of the Kaniv Reservoir in the Vytatchiv-Stajky region was carried out using the differential radar interferometry (DinSAR) technique. According to the results of observations during the spring period from 2015 to 2023, active landslide areas are displayed. The DinSAR method is briefly described, emphasising data filtering steps for landslide activation mapping. A high data correlation was recorded, and the presence of zones of active shifts on the shore of the reservoir was confirmed. The spread and intensity of landslide manifestations are determined by the peculiarities of the geological and geomorphological structure of the territory, its tectonic, neotectonic and seismic regimes, and hydrological and climatic conditions. Limitations of the method arising from the temporal decorrelation of the radar signal in regions with a large amount of vegetation are determined. Due to the significant decorrelation between the obtained results of forested and watered areas, the DinSAR technique, a digital elevation model (DEM), analysis of base surface maps and the results of spectral index calculations were combined to identify regions of active landslides caused by waterlogging of the Dnieper slopes. The study demonstrates the feasibility of using DinSAR to detect and monitor surface deformation.
Keywords: dangerous geological processes; landslides; monitoring; radar interferometry; GIS